195-Year History of Mykolayiv Observatory: Events and People - Shulga, O.V.; Yanyshevska, L.M. (Science and Innovation, 2024)
The basic stages of the history of the Mykolaiv Astronomical Observatory are shown. The main results of the Observatory activities are presented by the catalogs of star positions, major and minor planets in the Solar system, space objects in the Earth orbit. The information on the qualitative and quantitative structure of the Observatory, cooperation with the observatories of Ukraine and foreign countries as well as major projects carried out in the Observatory is provided.